PENGARUH STRUKTUR AKTIVA, PERTUMBUHAN, DANPROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN INDEKSLQ45 - Dinda Pramudyawasa Wardani (Politeknik Negeri Semarang, 2021)
The purpose of this study is to determine and analyze Asset Structure, Company Growth and Profitability simultaneously and partially affect the stock price of LQ45 Index companies listed on the Indonesia Stock Exchange in 2016-2018. The type of data used in this research is quantitative data. While the data source used is secondary data. The data used in this study were obtained from the annual financial report data of LQ45 Index companies listed on the Indonesia Stock Exchange for the 2016-2018 period. In this study, the data collection technique used by the researcher is the documentation method in the form of data stored on the official website www.idx.co.id. The analysis technique used in this research is multiple linear regression analysis technique. The results of this study indicate that simultaneously asset structure, company growth, and profitability have a significant effect on the LQ45 Index company's stock price on the Indonesia Stock Exchange in 2016-2018. While partially the variable that affects the stock price of LQ45 index companies on the Indonesia Stock Exchange in 2016-2018 is profitability.